Gynecologic Cancer InterGroup (GCIG) Consensus Review for Mucinous Ovarian Carcinoma. (1st November 2014) - Ledermann, Jonathan A.; Luvero, Daniela; Shafer, Aaron; O'Connor, Dennis; Mangili, Giorgia; Friedlander, Michael; Pfisterer, Jacobus; Mirza, Mansoor R.; Kim, Jae-Weon; Alexandre, Jerome; Oza, Amit; Brown, Jubilee
Abstract : Abstract: Mucinous carcinomas of the ovary can be primary or metastatic in origin. Improvements in the pathological diagnosis have increased the ability to distinguish between primary and metastatic ovarian cancers and shown that primary mucinous carcinomas are a rare subtype of ovarian cancer. Most tumors are diagnosed at an early stage, and the prognosis after surgery is good. Advanced or recurrent mucinous carcinoma of the ovary responds poorly to current cytotoxic treatments, and the prognosis is poor. Here, we review the guidelines for surgery and the results of treatment of advanced and recurrent disease. Chemotherapy with platinum and paclitaxel is currently used to treat advanced disease, but the effect of these drugs is modest, and new treatments are needed.